A critical study on the laws governing abandoned parents in Malaysia / Willson Peter and Nor Abilla Mahat - Willson, Peter; Mahat, Nor Abilla (2012)
The purpose of this study is to give a clear view about the current laws in Malaysia in administrating matters relating to the abandoned parents. This study will focus on the issue of inefficiency of these laws in protecting the rights of the abandoned parents as well as calling for the implementation of a specific act to govern this issue. This study also discloses the comparison between the laws relating to the abandoned parents in Malaysia to two other countries, namely Singapore and the United States. The aim of this study is to assist the legislator on improving the existing law to ensure that every aspect that may cause possible threat is well covered.